Pengaruh Pupuk Organik Cair (POC) Urine Kambing Terhadap Pertumbuhan Bibit Kakao ( Theobroma cacao L.) - Bayu Permadi (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2021)
The cocoa plant (Theobroma cacao L.) is one of the commodities that continues to be developed in Indonesia, but its production is still low due to poor fertilization, due to an increase in the use of chemical fertilizers, the purpose of this research is to determine the effect of liquid organic fertilizer from goat urine and tofu liquid waste for the growth of cocoa seedlings. The experimental design in this research is a randomized block design with two factors, the first factor is goat urine consisting of 3 levels, namely 0, 20, 40 ml / polybag the second factor is tofu liquid waste consisting of 3 levels. Ie 0, 60, 80ml / polybag, each treatment is repeated 3 times. The results of the study showed that the administration of goat urine and tofu liquid waste affected the growth of cocoa seedlings, the provision of liquid organic fertilizer from goat urine and tofu liquid waste at a dose of 40 ml / polybag and 80 ml / polybag significantly affected the number of leaves, leaf width and stem diameter. , giving liquid organic fertilizer from goat urine and tofu liquid waste did not significantly affect plant height. In the parameters of the number of leaves and stem diameter, there is an intraction between the two factors. Keywords: cocoa, seedlings, liquid organic fertilizer